Ezevent / Syazliana Kasim ... [et al.] - Kasim, Syazliana; Junos, Sutina; Ab Wahab, Shahrul Amri; Mohamad Ali, Noor Azillah; Othman, Farrah (Universiti Teknologi MARA, Kedah, 2019)
Event management can be a daunting task as there is a need to coordinate the multi-aspects of an event, starting from initiating, planning, executing, finalizing and reporting the event. Thus, EZEVENT is an event management kit developed to simplify the process of planning and organizing academic and non-academic events among UiTM users. It is well understood that there are numerous activities organized by faculties and the students in every academic semester. Naturally, the committee members will be different for each activity. In fact, not many would want to volunteer as a committee member as they are apprehensive about working around the event. To date, there is no all-in-one available reference for the committee members to use as a starting grid whenever they are trying to plan for an event. Premised on that concern, the major objectives of developing EZEVENT are to offer hassle-free event planning process and ensure the event runs smoothly, hence reducing the stress associated with the process. It is one-of-a-kind kit that can be personalized according to the users’ needs and requirements. Therefore, even if a person never had an experience of planning and organizing an event, this kit will become a handy guideline. There is a high potential of this kit being commercialized around the wide number of UiTM users and perhaps to external users of similar environment since in the market, there is no readily available kit that serve the same purpose.